(3MGTjI aj GdJaSjQs - (3GdLGHQOj, aNQ GdOjf, GdLGHQOj, CMeO Hf GdMSf Hf jhSa, J (B746(3g` (B1346(3es
(3ChdgG (B:s
(3ChdgG(B: (3hHYVce dHYV aJfI agh cbhdg agd CfJe efJghf HYO bhdg(B: (3EfeG GdNeQ hGdejSQ Edi BNQg hjOd Ydi gPG bhd GdTjNs
(3BNQgG (B:s
(3BNQgG(B: (3bhdg GdSdeGfjI, dCfg HfGgG GdTQja hgh ef Hfj SdjeGf, cGf ef ChdGO GdMSf Hf Ydj QVj Gddg YfgeG, bhdg GLjGO ZjQ efUQa GSe LHds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B1: 111s
(3cTa GdXfhf, L (B2: 1478s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs